Student impressions of instructors based on Zoom backgrounds: investigating perceived technology skills of instructors and affective learning of students - Kelly, Stephanie; Kim, Jihyun; Berry, Ian; Goke, Ryan (Frontiers in Computer Science, 2024)
The purpose of this study is to identify how Zoom backgrounds affect students’ affective learning and perceptions of an instructor’s technology use skills in online learning experiences. Data collected from undergraduate students in the U.S. indicate that with certain Zoom backgrounds, male students perceive the instructor having lower technology skills and experience less affective learning towards the instructor and course content than do female students. Overall, the study’s findings provide meaningful contributions to instructional communication research and suggest recommendations for strategic use of Zoom backgrounds to cultivate the best impression of an instructor and positive learning experiences.